2011
DOI: 10.1124/mol.111.074088
|View full text |Cite|
|
Sign up to set email alerts
|

α7β2 Nicotinic Acetylcholine Receptors Assemble, Function, and Are Activated Primarily via Their α7-α7 Interfaces

Abstract: We investigated assembly and function of nicotinic acetylcholine receptors (nAChRs) composed of ␣7 and ␤2 subunits. We measured optical and electrophysiological properties of wildtype and mutant subunits expressed in cell lines and Xenopus laevis oocytes. Laser scanning confocal microscopy indicated that fluorescently tagged ␣7 and ␤2 subunits colocalize. Fö rster resonance energy transfer between fluorescently tagged subunits strongly suggested that ␣7 and ␤2 subunits coassemble. Total internal reflection flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 36 publications
(75 reference statements)
8
56
1
Order By: Relevance
“…A significant difference was, however, found with the competitive antagonist DHbE. In agreement with this observation, the use of cysteine mutants indicated that this ligand does not bind in a functionally productive manner at the interface between a7 and b2 nAChR subunits (Murray et al, 2012), suggesting that only the a7-a7 nAChR subunit interface is able to activate the a7b2 nAChR heteromers and produce the ACh-evoked response. This result supports the observation that a7b2 nAChR heteromers show reduced maximal amplitudes of inward currents.…”
Section: The A7 Nicotinic Acetylcholine Receptor Heteromerssupporting
confidence: 60%
See 1 more Smart Citation
“…A significant difference was, however, found with the competitive antagonist DHbE. In agreement with this observation, the use of cysteine mutants indicated that this ligand does not bind in a functionally productive manner at the interface between a7 and b2 nAChR subunits (Murray et al, 2012), suggesting that only the a7-a7 nAChR subunit interface is able to activate the a7b2 nAChR heteromers and produce the ACh-evoked response. This result supports the observation that a7b2 nAChR heteromers show reduced maximal amplitudes of inward currents.…”
Section: The A7 Nicotinic Acetylcholine Receptor Heteromerssupporting
confidence: 60%
“…Recalling that ACh binds at the interface between two adjacent a7 nAChR subunits, novel and distinct subunit sites might be formed at the interface of a7 and other nAChR subunits. To tackle this question, it was shown that a7 and b2 nAChR subunits can assemble into functional heteromers that have pharmacological properties resembling a7 nAChR homomers but with lower maximal amplitudes of agonist-evoked currents (Murray et al, 2012). Evidence for heteromeric assembly included colocalization of tagged subunits using laser scanning confocal microscopy, fluorescence För-ster resonance energy transfer, and total internal reflection fluorescence microscopy.…”
Section: The A7 Nicotinic Acetylcholine Receptor Heteromersmentioning
confidence: 99%
“…This additional control has previously been used by us and others (Carbone et al, 2009;Eaton et al, 2014). If concatemer fragments were contributing to the functional nAChR population, the b 2 -gain-of-function subunit would assemble into resulting a 7 *-nAChR as previously shown (Khiroug et al, 2002;Murray et al, 2012;Zwart et al, 2014). Therefore, if fragments containing a 7 were present, this would result in appearance of a novel a 7 b 2 -gain-of-function population with distinctive (more agonist-sensitive) properties.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies using heterologous systems have shown that a 7 subunits can form functional channels when combined with a 5 (Girod et al, 1999), b 2 (Khiroug et al, 2002), b 3 (Palma et al, 1999), or b 4 subunits (Criado et al, 2012). Fluorescently tagged nAChR a 7 and b 2 subunits were recently used to characterize the formation of a 7 b 2 -nAChRs, and functional differences between a 7 -and a 7 b 2 -nAChRs have been suggested (Murray et al, 2012). Coexpression of b 2 and a 7 subunits caused a significant decrease in agonist-evoked whole cell current amplitudes, but this decrease occurs without affecting the concentration-response characteristics of a range of common agonists and antagonists (Murray et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation